Longitudinal user experience studies in the IoT domain: a brief panorama and challenges to overcome - Melo, Bianca; Andrade, Rossana; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2022: Anais do XXI Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2022)
User Experience (UX) is affected by users’ emotions, beliefs, and motivations, among other factors. Due to their subjective nature, these factors may influence UX over time and according to the different contexts where the interaction occurs. With the rising development of Internet of Things (IoT) systems to support daily activities and, at the same time, the increasing abandonment of these systems, the importance of ensuring good UX levels over time has become an even greater need. In this context, we conducted a snowballing procedure and systematic literature mapping to understand whether and how long-term UX evaluations have been conducted in IoT and the challenges and opportunities in conducting longitudinal studies in this field. We analyzed 55 papers that reported longitudinal evaluations in different IoT systems and 14 papers that reported UX evaluations in the IoT context. We also interviewed five software engineering professionals to learn about their IoT user-testing and evaluation perspectives. Our results provide a panorama of the conduction of longitudinal IoT studies and a glance at the directions the research on UX evaluation for IoT systems is taking. Hence, we indicate future research opportunities for evaluating long-term UX in IoT systems through the longitudinal approach, considering the complexity of these systems and their impact on users’ everyday lives.